Identifying opportunities to advance practice at a large academic medical center using the ASHP Ambulatory Care Self-Assessment Tool. (1st July 2018) - Martirosov, Amber Lanae; Michael, Angela; McCarty, Melissa; Bacon, Opal; DiLodovico, John R.; Jantz, Arin; Kostoff, Diana; MacDonald, Nancy C.; Mikulandric, Nancy; Neme, Klodiana; Sulejmani, Nimisha; Summers, Bryant B.
Abstract : Purpose: The use of the ASHP Ambulatory Care Self-Assessment Tool to advance pharmacy practice at 8 ambulatory care clinics of a large academic medical center is described. Summary: The ASHP Ambulatory Care Self-Assessment Tool was developed to help ambulatory care pharmacists assess how their current practices align with the ASHP Practice Advancement Initiative. The Henry Ford Hospital Ambulatory Care Advisory Group (ACAG) opted to use the "Practitioner Track" sections of the tool to assess pharmacy practices within each of 8 ambulatory care clinics individually. The responses to self-assessment items were then compiled and discussed by ACAG members. The group identified best practices and ways to implement action items to advance ambulatory care practice throughout the institution. Three recommended action items were common to most clinics: (1) identify and evaluate solutions to deliver financially viable services, (2) develop technology to improve patient care, and (3) optimize the role of pharmacy technicians and support personnel. The ACAG leadership met with pharmacy administrators to discuss how action items that were both feasible and deemed likely to have a medium-to-high impact aligned with departmental goals and used this information to develop an ambulatory care strategic plan. This process informed and enabled initiatives to advance ambulatory care pharmacy practice within the system. Conclusion: The ASHP Ambulatory Care Self-Assessment Tool was useful in identifying opportunities for practice advancement in a large academic medical center.